Modelagem e simulação de biorreator para produção de ácido fumárico - Fujimoto, Marisa Cristina Mendonça (Universidade Federal de São Carlos, 2018)
Considering the current scenario where there is a growing pressure for industry to include sustentability in its inegotiable values, several companies have been investing in research and development of new, environmentally friendly, processes. In the focus of innovation there are routes with smaller energy and solvent consumption, and reduced generation of waste. In this context, the present study aims at evaluating the production of fumaric acid via fermentation; the compound is an intermediate currently obtained from petrochemical raw materials. The study was based on extensive bibliographic research about the types of micro-organisms capable of producing the chemical, and an appropriate kinetic model to describe growth and accummulation of product was chosen. As an adequate kinetic model was not readily available in literature, a simple model was adjusted in the software SimulaFerm using experimental information reported in articles. Then, the bioreactor model was implemented in Scilab environment, making use of constitutive equations (kinetic models), and mass balances pertinent to transient operation. This software was chosen due to its interface with the process simulator COCO (CAPE-OPEN to CAPEOPEN), which does not comprise in its basic unit operations batch reactions commonly present in fermentations. With the results obtained, it was possible to better understand the limitations and opportunities regarding the production of fumaric acid through this alternative route.
Modeling and simulation of a bioreactor for fumaric acid production
Keywords: Modelagem e simulação; Ácido fumárico; Modeling and simulation; Fumaric acid; ENGENHARIAS::ENGENHARIA QUIMICA